Training Engagement Intensity and Prosocial Character Among Young Taekwondo Participants - Rizqi Agus Kurniawan; Elda Pradana Tika; Ifada Novikasari; Umti Hamimah; Rizqi Agustina Setyaningrum; Irfan Musonif (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The increasing complexity of children’s psychosocial development in the digital era has intensified concerns regarding discipline, self-control, and prosocial behavior among young individuals. This study aimed to examine the statistical association between taekwondo training engagement intensity and children’s prosocial character among members of Dojang Golden Eagle. The study employed a quantitative cross-sectional correlational design involving 50 child and adolescent taekwondo participants selected using a total sampling approach. Data were collected through structured self-report questionnaires measuring training engagement intensity and children’s character dimensions, including discipline, responsibility, self-control, social respect, and self-confidence. Construct validity was evaluated using Exploratory Factor Analysis, while reliability was assessed using Cronbach’s Alpha coefficients. Multiple regression analysis was conducted after assumption testing procedures were satisfied. The findings indicated that training engagement intensity was positively and significantly associated with children’s character scores after controlling for demographic variables (β = .682, p = .001). The regression model explained 43.2% of the variance in character outcomes. The findings suggest that consistent participation in structured taekwondo training environments may be associated with stronger prosocial self-regulatory characteristics among children. Nevertheless, causal interpretations should be made cautiously due to the cross-sectional nature of the study.